Effects of the combined application of vermicompost organic fertilizer on tomato growth, nitrogen utilization and soil fertility in greenhouses(蚯蚓粪肥配施对设施番茄生长、氮素利用和土壤肥力的影响) - LIU Chanjuan(刘婵娟); YE Fang(叶放); XU Shun’an(徐顺安); LI Zhesi(李喆思); LIU Yaru(刘雅茹); HUANG Lukuan(黄路宽); LIU Qizhen(刘奇珍); FENG Ying(冯英) (浙江大学学报. 农业与生命科学版, 2025)
To investigate the synergistic effects of chemical fertilizer reduction and vermicompost organic fertilizer application, a greenhouse field experiment was conducted to compare the effects of the combined application of different proportions of vermicompost organic fertilizer under equal nitrogen conditions on tomato yield, quality, nitrogen absorption and utilization, and soil fertility. The results showed that the combined application of vermicompost organic fertilizer not only increased the soil pH value, organic matter content and cation exchange capacity, but also increased the soil urease and catalase activities. Compared with conventional fertilization (CF), the combined application of vermicompost organic fertilizer improved the yield and quality of tomato. Among them, the combined application of 25% vermicompost organic fertilizer (V1) increased the yield by 10.67%, while the vitamin C content, total soluble solid content and solidity-acid ratio of the fruits increased by 34.97%, 15.95%, and 13.76%, respectively. Compared with those in the CF treatment, the nitrogen fertilizer utilization efficiency and agronomic utilization efficiency increased by 37.00%-128.36% and 159.87%-165.62%, respectively, after the combined application of vermicompost organic fertilizer, among which the V1 treatment was the best. Correlation analysis showed that both tomato yield and nitrogen use efficiency were significantly correlated with soil quality and enzyme activity. Based on a comprehensive analysis of yield, quality and nitrogen use efficiency, chemical fertilizer combined with 25% vermicompost organic fertilizer is the best fertilization treatment to reduce the application of chemical fertilizer, improve yield and quality, and fertilize the soil in greenhouses.(为研究化肥减施与蚯蚓粪肥配施的增效作用，采用温室大棚田间试验，比较了等氮条件下配施不同比例蚯蚓粪肥对番茄产量、品质、氮素吸收利用及土壤肥力的影响。结果发现：配施蚯蚓粪肥提高了土壤pH值、有机质含量和阳离子交换量，增加了土壤脲酶和过氧化氢酶活性。与常规施肥（CF）相比，配施蚯蚓粪肥提升了番茄产量和品质，其中配施25%蚯蚓粪肥处理（V1）表现最优，产量增加了10.67%，果实的维生素C含量、可溶性固形物含量和固酸比分别提高了34.97%、15.95%和13.76%。配施蚯蚓粪肥处理的氮肥利用率和氮肥农学利用率较CF处理分别提升了37.00%～128.36%和159.87%～165.62%，以V1处理的增幅最大。相关性分析表明，番茄产量和氮素利用效率与土壤质量及酶活性显著相关。综合分析产量、品质和氮肥利用率等指标，配施25%蚯蚓粪肥是减少设施番茄化肥施用、实现增产提质、培肥土壤的最佳施肥处理。)